Cocoa farming households in Ghana consider organic practices as climate smart and livelihoods enhancer. Issue 1 (December 2016) - Bandanaa, Joseph; Egyir, Irene; Asante, Isaac
Abstract Background Several state and non-state organizations are promoting organic agriculture as a climate smart option among cocoa farmers in the Ashanti region of Ghana. In this study, flora diversity and livelihoods position in organic and conventional farming were measured and compared. The experiment included 32 households with young plantations. Jaccard similarity, Shannon (H ′) and Simpson (D ) diversity indices were measured to assess species similarity, abundance, evenness and dominance. The sustainable livelihoods indicators were food security, income, vulnerability and well-being. Results The results showed that the species are quite similar. TheH ′ index for organic farms was slightly higher (0.808) than that of conventional farms (0.762); theD index (0.051) for organic was better than the conventional (0.084). The organic farmers studied had better sustainable livelihoods outcomes than the conventional farmers. Conclusion Since organic farming has more biodiversity, farmers should be encouraged to practise it to improve livelihoods outcomes and enhance climate change mitigation.